Intraspecific variation in seed morphology of tribe vicieae (Papilionoidae) using scanning electron microscopy techniques. Issue 3 (27th December 2017) - Rashid, Neelam; Zafar, Muhammad; Ahmad, Mushtaq; Malik, Khafsa; Haq, Ihsan‐ul; Shah, Syed Nasar; Mateen, Abdul; Ahmed, Tauseef
Abstract: Seed micromorphology of 12 species of tribe Vicieae (Papilionoidae) representing five genera were examined using Scanning Electron Microscope (SEM). The different seed types were described, illustrated, compared, and their taxonomic importance is discussed. Seeds exhibit great diversity in ultrastructure and a variety of novel morphological features have been determined among and within genera of the tribe. Seeds were characterized by oval to round shape, ovate to oblong outline and striate to papillate ornamentation. Radiate and wavy cell pattern has been observed as a characteristic exomorphological feature. In Vicia sativa, testa cells superficially seem to form peltate hairs. As a result, seed micromorphology with few exceptions showed variation and its taxonomic value was significant in distinguishing taxa at species level. The disparity in shape and density of papillae or protuberances and alignment of testa cells, may possibly give further insight at intraspecific level within tribe. The findings also illustrated that the use of SEM in seed morphology can reveal hidden morphological affinities among species and showed potential in delimitation of Vicieae members generally at tribe, genus, and particularly at species level. Abstract : This study is focused on seed morphological and ultrastructural aspects in five genera and 12 species of tribe Vicieae . The seeds were characterized by oval to round shape, ovate or oblong outline, striate to papillate ornamentation, and wavy cell margin. Two distinctive cell patterns were observed; radiate and wavy, the testa cells in Vicia sativa superficially seem to form peltate hairs.